2011
DOI: 10.1021/ol2011083
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Conventional and Unconventional Water Dimers by Water-Binding Foldamers

Abstract: Water-binding foldamers have been rarely studied. By orienting both H-bond donors and acceptors toward their interior, two pyridine-derived crescent-shaped folding oligoamides were found to be capable of trapping both conventional and unconventional water dimer clusters in their cavity (∼2.5 Å radius). In the unconventional water dimer cluster, the two water molecules stay in contact via an unusual H-H interaction (2.25 Å) rather than the typical H-bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 62 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…19,20 Concurrent with the rapid diverse structural elaborations by one-pot H-bonding-assisted macrocyclization, 19 varying functions have also been demonstrated that include selective binding of inorganic [21][22][23] and organic 24 cations in high affinity, formation of highly conducting transmembrane pores, 25 tight associations with neutral molecules such as fullerenes/ coronene 26 and p-toluenesulfonic acid, 27 and stabilization of G-quadruplex structures. 28 To further expand the structural diversity of H-bonded macrocycles and their potentially realizable functions and applications, we have also reported a series of crescent-shaped or helically folded molecular strands derived from methoxybenzene, [29][30][31][32] pyridone, 22,33 fluorobenzene 34,35 and pyridine motifs [36][37][38][39][40][41] with their aromatic backbones rigidified by internally placed continuous H-bonding networks. With additional backbone confinement via a covalent macrocyclization, the appropriately sized pentamers can become circularly folded to arrive at a unique pentagon shape.…”
Section: Ying Liumentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Concurrent with the rapid diverse structural elaborations by one-pot H-bonding-assisted macrocyclization, 19 varying functions have also been demonstrated that include selective binding of inorganic [21][22][23] and organic 24 cations in high affinity, formation of highly conducting transmembrane pores, 25 tight associations with neutral molecules such as fullerenes/ coronene 26 and p-toluenesulfonic acid, 27 and stabilization of G-quadruplex structures. 28 To further expand the structural diversity of H-bonded macrocycles and their potentially realizable functions and applications, we have also reported a series of crescent-shaped or helically folded molecular strands derived from methoxybenzene, [29][30][31][32] pyridone, 22,33 fluorobenzene 34,35 and pyridine motifs [36][37][38][39][40][41] with their aromatic backbones rigidified by internally placed continuous H-bonding networks. With additional backbone confinement via a covalent macrocyclization, the appropriately sized pentamers can become circularly folded to arrive at a unique pentagon shape.…”
Section: Ying Liumentioning
confidence: 99%
“…12d). By further combining these cation binders with the pyridine-based motifs recently developed in our lab, [36][37][38][39][40][41] more diverse structures can be created. The ability to do so should lead to a new generation of macrocyclic receptors that feature the variable components in their main chain backbone and that are possibly endowed with the highly tunable cation-binding affinities.…”
Section: Pyridone-based Pentamers 22mentioning
confidence: 99%
“…Importantly, this small cavity, which is decorated by many hydrogen‐bond donors and acceptors, matches well with the diameter of a water molecule. Accordingly, pyridine pentamers such as 1 take a helically folded structure (Figure a) . Upon introducing two “sticky ends” at helical ends, numerous molecules of 1 self‐assemble, by intermolecular hydrogen bonds among the sticky ends, into a one‐dimensionally stacked nanotubular structure, which is capable of accommodating a hydrogen‐bonded single‐file water chain in the hollow cavity (Figure b).…”
Section: Introductionmentioning
confidence: 99%
“…However, amination followed by carboxylation clearly complicates the isolation of pure material and we thought to reverse these steps, thus starting from ferrocene-1,1'-dicarboxylic acid. Although dicarboxylic acids are classical substrates to access carbamate-protected amino acids, their desymmetrization are usually performed by bis-ester saponification, [41][42][43] mono-ester formation 44 or cyclic anhydride opening (either with an azide or NH3) reactions. [45][46][47] All these approaches require multiple steps, and shorter routes have been less studied.…”
Section: Introductionmentioning
confidence: 99%